2023
DOI: 10.4103/jfmpc.jfmpc_193_22
|View full text |Cite
|
Sign up to set email alerts
|

Myths, beliefs, and attitude toward cancer among the family caregivers of cancer patients: A community-based, mixed-method study in rural Tamil Nadu

Abstract: A BSTRACT Background and Aim: Family support is one of the most crucial components of cancer care. The familial beliefs and myths associated with cancer can seriously affect the quality of life and treatment outcome of cancer patients. This study intends to explore the prevailing myths, beliefs, and attitude toward cancer among the family caregivers of cancer patients. Materials and Methods: A community-based, exploratory, mixed-method study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…We employed the same questionnaire and five-point Likert scale as the ones used by Ajith et al . [ 8 ] in a previous study (strongly agree, agree, neutral, disagree, and strongly disagree). For purposes of analysis, the responses agree and strongly agree were combined; similarly, disagree and strongly disagree were put together, while neutral was considered as a group.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We employed the same questionnaire and five-point Likert scale as the ones used by Ajith et al . [ 8 ] in a previous study (strongly agree, agree, neutral, disagree, and strongly disagree). For purposes of analysis, the responses agree and strongly agree were combined; similarly, disagree and strongly disagree were put together, while neutral was considered as a group.…”
Section: Discussionmentioning
confidence: 93%
“…[ 7 ] There are several myths surrounding the condition, and the associated stigma has far-reaching implications for the people affected and their caretakers. [ 8 ] A lack of knowledge, generally worse in the rural areas, can cause significant barriers to accessing health care and often neglect, especially for the elderly cancer patients. The elderly, dependent on care from the younger members of the family, face stigma leading to neglect, resulting ultimately in poor treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, people who know someone with cancer might have more exposure to non–evidence-based information as they seek knowledge and are more receptive to messages around CRC, making them more vulnerable to misinformation. 47 , 48 , 50 In Middle Eastern countries, families play an important role in medical and lifestyle decisions made by patients, which can affect treatment options and opportunities for care. 6 , 51 Families are often the main carers for patients diagnosed with cancer in the Middle East and also take responsibility for treatment, 6 compared with Western countries, where care and treatment choices are more strongly dependent on patient preferences and where hospices or nursing homes are more acceptable and available.…”
Section: Discussionmentioning
confidence: 99%
“…It is also believed that cancer results from injuries that can be transmissible/ inherited and spread by cutting through it. 47 These myths and misconceptions vary across countries in Africa and present significant barriers to cancer control as cancer risk prevention lifestyle changes, screening, and treatment are ignored. 48 The reports from different African countries have indicated that religion and sociocultural beliefs contribute immensely to the myths and misconceptions about diseases in general 49,50 and cancer in particular.…”
Section: Common Myths On Cancers In Nigeriamentioning
confidence: 99%
“…It is thought that cancers are the result of past sins, wizardry/witchcraft, evil eye, evil arrows, curse, envy, and forth. It is also believed that cancer results from injuries that can be transmissible/inherited and spread by cutting through it 47 . These myths and misconceptions vary across countries in Africa and present significant barriers to cancer control as cancer risk prevention lifestyle changes, screening, and treatment are ignored 48 …”
Section: Common Myths On Cancers In Nigeriamentioning
confidence: 99%